Geology of Euphrates Formation and its Economic Importance - Khdhair, Dalia Kareem; Awadh, Salih M. (Iraqi Journal of Science, 2025)
This research aims to give an overview of the whole of the Euphrates Formation in Iraq. The deposition of the Euphrates Formation continued for approximately 10 million years, extending from the Early Miocene to the Middle Miocene epoch, including the Aquitanian- Langhian stages (23.3 - 13.82 M.Y ago). The formation is distributed regionally, as it includes about 75% of Iraq and extends to neighbouring countries, as it is equivalent to the Asmari Formation in Iran, while it is equivalent to the Hadroukh and Hofuf formations in Saudi Arabia and Jourdan. Syria is still named the Euphrates Formation, with 200 m thick overlying the Chilou Formation. In central Iraq and Kirkuk, it is equivalent to the Serikagni Formation. The predominant facies of the formation are limestone and marl with dolomization of varying intensity in various locations deposited in a wide range of the marine environment extended from lagoon to open marine. The formation has economic importance; in subsurface sites, it is an oil reservoir, such as in northern Iraq, or an aquifer in western and southern Iraq, in addition to the possibility of using its rocks in multiple industries, most notably in building and construction.